2004
DOI: 10.1016/s1074-7613(04)00022-6
|View full text |Cite
|
Sign up to set email alerts
|

SOCS3 Is a Critical Physiological Negative Regulator of G-CSF Signaling and Emergency Granulopoiesis

Abstract: To determine the importance of suppressor of cytokine signaling-3 (SOCS3) in the regulation of hematopoietic growth factor signaling generally, and of G-CSF-induced cellular responses specifically, we created mice in which the Socs3 gene was deleted in all hematopoietic cells. Although normal until young adulthood, these mice then developed neutrophilia and a spectrum of inflammatory pathologies. When stimulated with G-CSF in vitro, SOCS3-deficient cells of the neutrophilic granulocyte lineage exhibited prolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
273
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(303 citation statements)
references
References 45 publications
(2 reference statements)
29
273
1
Order By: Relevance
“…Mice with point mutations in S727 of STAT3 and Y757 of gp130 have been described in detail (15,16). The suppressor of cytokine signaling (SOCS) gene in Socs3 Ϫ/fl ; lysMcre or Socs3 ϩ/fl ; lysMcre mice have been described previously (17). Socs3 fl/fl ; lysMcre mice were bred at St. Jude Children's Research Hospital and used as a source of macrophages for the remaining experiments.…”
Section: Mice and Macrophage Isolationmentioning
confidence: 99%
“…Mice with point mutations in S727 of STAT3 and Y757 of gp130 have been described in detail (15,16). The suppressor of cytokine signaling (SOCS) gene in Socs3 Ϫ/fl ; lysMcre or Socs3 ϩ/fl ; lysMcre mice have been described previously (17). Socs3 fl/fl ; lysMcre mice were bred at St. Jude Children's Research Hospital and used as a source of macrophages for the remaining experiments.…”
Section: Mice and Macrophage Isolationmentioning
confidence: 99%
“…30 All cells were cultured in 0.3% agar in Dulbecco modified Eagle medium (DMEM) containing 20% FCS. Cytokines were used at the final concentrations of 10 ng/mL murine IL-3, 100 ng/mL murine SF, 2 U/mL rhEpo, and 10 ng/mL murine granulocyte macrophage (GM)-CSF.…”
Section: Clonogenic Progenitor Cell Assaysmentioning
confidence: 99%
“…[19][20][21] In myeloid cells, Socs3 has been demonstrated to be an important attenuator of signaling by granulocyte colony-stimulating factor (G-CSF). 22,23 Within mammary epithelium, Socs3 expression is induced to varying magnitudes by PRL and EGF, with the highest induction occurring in response to EGF stimulation in both the mammary gland and HC11 mouse epithelial cells. 24 Expression profiling analyses of the different stages of mammary gland involution showed that Socs3 was highly upregulated during the first four days of this phase.…”
Section: Introductionmentioning
confidence: 99%